How does materialistic attitude influence the impact of corporate brand on the customers' intention to donate to corporates' charity?. Issue 4 (13th November 2017) - Pratono, Aluisius Hery; Tjahjono, Godo
Abstract : Purpose: The purpose of this paper is to determine the impact of corporate brand equity and corporate brand credibility on customer's intention to donate the charity program. To understand the complex relationship, this study points out the moderating effect of the materialistic attitude. Design/methodology/approach: The empirical study involved a survey of young customers in Indonesia telecommunication industry. The data collection involved face-to-face interviews among 409 respondents in Jakarta Indonesia between December 2015 and January 2016. Findings: This study indicates a positive impact of corporate brand equity and brand credibility on their customers' intention to support the social charity. However, materialistic attitude slightly changes the impact direction of corporate brand on the customers' intention to participate. Research limitations/implications: This research relies on a cross-sectional observation, which was one snapshoot observation in specific time. Second, this study uses interview to help the respondents understand the questionnaires; this may imply on the level of objectiveness of respondents. Practical/implications: This paper extends the discussion on the altruism theory and corporate brands by establishing a critical linkage between materialistic attitude, corporate brand credibility and consumers' intention to charity. Under high materialistic attitude, corporations are encouraged to promote strong business ethics. Originality/value: This study makes a contribution to the deepening understanding on altruism theory and conscious corporate responsibility through raising a concern on marketing practices, which entails a potential fraud from charity ethics.